Early impact of COVID-19 outbreak on eye care: Insights from EUROCOVCAT group. Issue 1 (January 2021) - Toro, Mario Damiano; Brézin, Antoine Pierre; Burdon, Michael; Cummings, Arthur Bernard; Evren Kemer, Ozlem; Malyugin, Boris Edvard; Prieto, Isabel; Teus, Miguel Angel; Tognetto, Daniele; Törnblom, Riikka; Posarelli, Chiara; Chorągiewicz, Tomasz; et al.
The recent outbreak of coronavirus disease 2019 (COVID-19) has been declared a public health emergency worldwide. The scientific community has put in much effort and published studies that described COVID-19's biology, transmission, clinical diagnosis, candidate therapeutics, and vaccines. However, to date, only a few data are available on the impact of COVID-19 pandemic on ophthalmological care in different health care systems, its future consequences in terms of disability, and access to sight-saving cures for many patients. To reduce human-to-human transmission of the virus and also ensure supply of infrastructures, human resources, and disposable medical devices to many regions, it is crucial to assess risks and postpone non-essential outpatient visits and elective surgical procedures, especially in older patients and those with comorbidities. This delay or suspension in essential eye procedures may cause significant and rapid vision impairment to irreversible blindness. Determining the risk-benefit profile of treating these ocular pathologies is a public health issue of supreme priority, even though many patients benefiting from therapeutic treatments are elderly, who are more vulnerable to COVID-19. If not reversible, this process could lead to a dramatic increase in disability and unsustainable social costs for many Governments.